Pemenuhan Hak Administrasi Kependudukan bagi Orang dengan Gangguan Jiwa di Desa Kalirejo, Kecamatan Talun, Kabupaten Pekalongan - Savana, Allaily Nuzulia; Qomariyah, Siti (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The fulfillment of civil registration rights for people with mental disorders (ODGJ) in Kalirejo Village, Talun Subdistrict, Pekalongan Regency, is an important issue that requires serious attention. Based on Law Number 23 of 2006 concerning Civil Registration, every Indonesian citizen has the right to obtain civil documents such as an Identity Card (KTP) and Family Card (KK). However, in practice, many individuals with mental disorders in Kalirejo Village lack these essential documents, preventing them from accessing social and healthcare services that are their rightful entitlements. This study aims to analyze the factors contributing to the non-fulfillment of civil registration rights for ODGJ, as well as the implications arising from this situation. The research employs a qualitative approach with an empirical juridical method. Primary data were collected through interviews with village officials, families of ODGJ, and direct observations in Kalirejo Village, while secondary data included legal documents and literature related to the fulfillment of civil registration rights. The findings reveal that the main barriers to the fulfillment of these rights are the low level of legal awareness among the community and the limited proactive efforts by village authorities. The implications of this situation include restricted access for ODGJ to healthcare and social assistance services to which they are entitled, worsening their health conditions and increasing social marginalization within the community.